2011
DOI: 10.1038/nrd3504
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer metabolism: a therapeutic window opens

Abstract: PrefaceGenetic driver events in cancer activate signaling pathways that alter cell metabolism. Clinical evidence has linked metabolism with cancer outcomes.Together, this has raised interest in targeting metabolic enzymes for cancer therapy, but also concerns that these therapies would have unacceptable effects on normal cells. However, some of the first cancer therapies target the specific metabolic needs of cancer cells and remain effective agents used in the clinic today. Research to understand how changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
1,092
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,280 publications
(1,116 citation statements)
references
References 161 publications
16
1,092
1
7
Order By: Relevance
“…In summary, the present results support the hypothesis that targeting cancer metabolism by simultaneously inhibiting 3 key metabolic pathways may actually have a wide therapeutic window (26), as no unacceptable effects in mice were observed when treated at translated doses slightly below to those used in patients for LND and DON administered separately. Notably, DON and LND are drugs that are currently being re-studied (27)(28)(29), while formulations of orlistat suitable for systemic administration have been investigated (19).…”
Section: Discussionsupporting
confidence: 74%
“…In summary, the present results support the hypothesis that targeting cancer metabolism by simultaneously inhibiting 3 key metabolic pathways may actually have a wide therapeutic window (26), as no unacceptable effects in mice were observed when treated at translated doses slightly below to those used in patients for LND and DON administered separately. Notably, DON and LND are drugs that are currently being re-studied (27)(28)(29), while formulations of orlistat suitable for systemic administration have been investigated (19).…”
Section: Discussionsupporting
confidence: 74%
“…33 In addition, clinical studies also have provided evidence of a close relationship between altered cellular metabolism and the cancer outcome. 34 Reactive oxygen species (ROS), which are generated by mitochondrial oxidative phosphorylation, was reported to limit the life span of HSCs. 35 However, mitochondrial ROS levels in HSCs were not increased before the development of disease by the overexpression of Fbxl10, as examined by flow cytometry using a fluorogenic molecular probe (supplemental Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…the Warburg effect. Indeed, it has been suggested that specifically targeting cancer cell metabolism may reveal therapeutic opportunities (Vander Heiden 2011). Most tumour cells are predominantly glycolytic for ATP supply and provision in metabolic precursors for macromolecule biosynthesis, whereas in terminally differentiated fibroblasts, where biosynthetic demands are lower, ATP synthesis is predominantly mitochondrial in origin, as outlined by Warburg so many years ago.…”
Section: Introductionmentioning
confidence: 99%